Joint time and beam domain non-orthogonal multiple access - Zhaoyang ZHANG; Jiajia WU; Jue WANG; Chu ZHOU (Tongxin xuebao)
In order to improve the system’s ability to accommodate connected devices, a joint time and beam domain non-orthogonal multiple access (NOMA) scheme was proposed, which was suitable for millimeter wave massive multiple-input multiple-output (MIMO) systems.The correlation and difference of the users’ channel were utilized to realize beam-domain NOMA, and sparse spreading technology was utilized to realize time-domain NOMA.With the optimization goal of improving the communication reliability of the system, optimization problem of the joint domain sparse access matrix design was constructed and solved.Finally, the access matrix was reconstructed based on the channel quality of the joint domain, and the interference cancellation operation was added to the message passing algorithm (MPA), which reduced the decoding complexity and improves the communication reliability.